Anti-Neurotrophic Effects from Autoantibodies in Adult Diabetes Having Primary Open Angle Glaucoma or Dementia - Zimering, Mark B.; Moritz, Thomas E.; Donnelly, Robert J. (Frontiers in Endocrinology, 2013)
Aim: To test for anti-endothelial and anti-neurotrophic effects from autoantibodies in subsets of diabetes having open-angle glaucoma, dementia, or control subjects. Methods: Protein-A eluates from plasma of 20 diabetic subjects having glaucoma or suspects and 34 age-matched controls were tested for effects on neurite outgrowth in rat pheochromocytoma PC12 cells or endothelial cell survival. The mechanism of the diabetic glaucoma autoantibodies’ neurite-inhibitory effect was investigated in co-incubations with the selective Rho kinase inhibitor Y27632 or the sulfated proteoglycan synthesis inhibitor sodium chlorate. Stored protein-A eluates from certain diabetic glaucoma or dementia subjects which contained long-lasting, highly stable cell inhibitory substances were characterized using mass spectrometry and amino acid sequencing. Results: Diabetic primary open angle glaucoma (POAG) or suspects (n = 20) or diabetic dementia (n = 3) autoantibodies caused significantly greater mean inhibition of neurite outgrowth in PC12 cells (p < 0.0001) compared to autoantibodies in control diabetic (n = 24) or non-diabetic (n = 10) subjects without glaucoma (p < 0.01). Neurite inhibition by the diabetic glaucoma autoantibodies was completely abolished by 10 μM concentrations of Y27632 (n = 4). It was substantially reduced by 30 mM concentrations of sodium chlorate (n = 4). Peak, long-lasting activity survived storage ×5 years at 0–4°C and was associated with a restricted subtype of Ig kappa light chain. Diabetic glaucoma or dementia autoantibodies (n = 5) caused contraction and process retraction in quiescent cerebral cortical astrocytes effects which were blocked by 5 μM concentrations of Y27632. Conclusion: These data suggest that autoantibodies in subsets of adult diabetes having POAG (glaucoma suspects) and/or dementia inhibit neurite outgrowth and promote a reactive astrocyte morphology by a mechanism which may involve activation of the RhoA/p160 ROCK signaling pathway.